Incidence, prevention, and management of complications following percutaneous nephrolitholapaxy - Seitz, Christian; Häcker, Axel (European urology, 2012)
Context: Incidence, prevention, and management of complications of percutaneous nephrolitholapaxy (PNL) still lack consensus. Objective: To review the pidemiology of complications and their prevention and management. Evidence acquisition: A literature review was performed using the PubMed database between 2001 and May 1, 2011, restricted to human species, adults, and the English language. The Medline search used a strategy including medical subject headings (MeSH) and free-text protocols with the keywords percutaneous, nephrolithotomy, PCNL, PNL, urolithiasis, complications, and Clavien, and the MeSH terms nephrostomy, percutaneous/adverse effects, and intraoperative complications or postoperative complications. Evidence synthesis: Assessing the epidemiology of complications is difficult because definitions of complications and their management still lack consensus. For a reproducible quality assessment, data should be obtained in a standardized manner, allowing for comparison. An approach is the validated Dindo-modified Clavien system, which was originally reported by seven studies. No deviation from the normal postoperative course (Clavien 0) was observed in 76.7% of PNL procedures. Including deviations from the normal postoperative course without the need for pharmacologic treatment or interventions (Clavien 1) would add up to 88.1%. Clavien 2 complications including blood transfusion and parenteral nutrition occurred in 7%; Clavien 3 complications requiring intervention in 4.1.%; Clavien 4, life-threatening complications, in 0.6%; and Clavien 5, mortality, in 0.04%. High-quality data on complication management of rare but potentially debilitating complications are scarce and consist mainly of case reports. Conclusions: Complications after PNL can be kept to a minimum in experienced hands with the development of new techniques and improved technology. A modified procedure-specific Clavien classification should be established that would need to be validated in prospective trials.
Published online ahead of print on September 28, 2011
Gesehen am 03.07.2018